ANALISIS POTENSI DAN KARAKTERISTIK GAMBUT SEBAGAI BAHAN PERTIMBANGAN UNTUK ARAHAN PERENCANAAN PENGEMBANGAN KAWASAN DI KABUPATEN SIAK - Soewandita, Hasmana; sudiana, nana (Jurnal Sains dan Teknologi Indonesia, 2011)
Peat land resources have the potential to be managed sustainably. Peatlands as a fragile ecosystem utilization should consider its characteristics, such as depth, maturity, fertility, land cover conditions, and calorie content. Peatland resources located in Siak Regency is a land system called Mendawai (MDW) and Gambut (GBT), whereas according to the USDA classification (2003) is land unit called Tropofibrist, Tropohemist and Troposaprist. For further management, peatland area in Siak District grouped into 7 regions peat dome : Buatan, Bukit Batu, Kandis, Merempan, Siak Kecil, Sungai Mandau and Zamrud. Based on the level of soil fertility, maturity and depth of peat, the peat areas suitable for agricultural development is the Siak Kecil, Sungai Mandau and Zamrud. Considering the condition of land cover and ecosystem components, Zamrud peat dome should be allocated to the conservation area. While based on calorie content and level of maturity, Mandau and Buatan peat dome are suitable for industrial development of peat-based materials